2021
DOI: 10.1111/sum.12769
|View full text |Cite
|
Sign up to set email alerts
|

The role of biochar in improving soil properties, water retention and potato yield in a Fluvisol under temperate monsoon climate

Abstract: Long-term cultivation without appropriate soil, water and nutrient management leads to the depletion of essential elements and soil organic matter, which can reduce crop yields. In this regard, soil amendment with biochar presents great potential for improving soil chemical properties through the initial addition of soluble and organically bound nutrients such as N, P, K, Ca, and Mg, which are labile fractions and supplied through mineralization of nutrients with time (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Several studies found that amending soils with biochar caused an improvement in seed germination as well as the growth and crop yield of many plants [ 73 , 74 ]. The amelioration of growth and productivity of plants in many sandy soils due to the additions of biochar is caused by many reasons: reducing bulk density as well as increasing total porosity and water holding capacity [ 75 , 76 ], improving water use efficiency [ 77 ], it also enhances nutrient availability, organic matter, and cation exchange capacity [ 20 , 22 , 44 ], and improves soil biological properties [ 78 ]. In this study, it is obvious that applying biochar at 5% decreased the yield parameters of red radish plants in comparison with the rest of the treatments which may be attributed to the increased salt concentrations retained by the soil after using saline water in irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that amending soils with biochar caused an improvement in seed germination as well as the growth and crop yield of many plants [ 73 , 74 ]. The amelioration of growth and productivity of plants in many sandy soils due to the additions of biochar is caused by many reasons: reducing bulk density as well as increasing total porosity and water holding capacity [ 75 , 76 ], improving water use efficiency [ 77 ], it also enhances nutrient availability, organic matter, and cation exchange capacity [ 20 , 22 , 44 ], and improves soil biological properties [ 78 ]. In this study, it is obvious that applying biochar at 5% decreased the yield parameters of red radish plants in comparison with the rest of the treatments which may be attributed to the increased salt concentrations retained by the soil after using saline water in irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar has been recognized for its carbon capture and storage in the special report of the Intergovernmental Panel on Climate Change (IPCC) (Schmidt et al 2018). Recently, several studies have reported biochar as a soil enhancer for improving crop yield due to its ability to retain moisture and improve water-holding capacity for droughtresilient agriculture (Blanco-Canqui 2017; Kassaye et al 2021;Martinsen et al 2015). Similarly, biochar enhances soil fertility because of the in situ soluble, organically bound nutrients (Abbaszadeh-Dahaji et al 2019;Karimi et al 2020).…”
Section: Introductionmentioning
confidence: 99%